A low-power DSP core-based software radio architecture. - Gunn, J.E (IEEE Journal on selected areas in communications)
This paper describes an approach to developing a low-power digital signal processor (DSP) subsystem architecture for advanced software radio platforms. The architecture is intended to support next-generation wide-band spread-spectrum military waveforms. The methodology illustrates how a next-generation programmable DSP core forms the basis for an application-specific integrated circuit (ASIC). It also shows how semiconductor technologies can be integrated into such chips to achieve algorithm performance while minimizing subsystem power consumption. The ASIC is run-time configurable to maintain high flexibility. The range of RF channel modulation (?waveforms?) and air interfaces is intended to include both wide-band and traditional narrow-band waveforms. Estimated gate counts and power-consumption estimates are presented. DSP circuit-design and power-management strategies necessary to achieve low-power operation are presented. While the architecture discussion focuses on military waveforms, the approach is also applicable to commercial waveforms